Process Management A Guide for the Design of Business Processes - Becker, Jörg; Kugeler, Martin; Rosemann, Michael (Springer Berlin Heidelberg, 2003)
Process Management is a comprehensive compendium for the contemporary design of process-oriented organizations. It presents a proven methodology for the introduction and sustainable management of business processes. This book discusses each phase of a business process lifecycle model in the light of current research. A continuous case study provides interesting insights into the actual experiences with this lifecycle model and adds to the credibility of the presented contents. This also includes recommendations which are summarized in pragmatic checklists for each stage of the project. This book is of relevance for business analysts, business process managers, consultants, and all practitioners dealing with the analysis and re-design of business processes. It is also a valuable resource for lecturers and students in the disciplines of Business, Information Systems and Engineering